Readjusting trade-offs among criteria in internal ratings of credit-scoring:an empirical essay of risk analysis in mortgage loans - Ferreira, Fernando A. F. (2020)
Credit-scoring becomes increasingly important in poor economies and recessions. Decreasing liquidity due to reduced access to both money and debt markets has induced banks to impose restrictions on offering credit, including credit for mortgage loans. In this paper we analyze the internal rating system used by one of the top-five banks in Portugal, and propose a methodological framework which, based on an application of the Delphi technique, allows adjusting trade-offs among evaluation criteria and provides decision makers with a fairer, more accurate and transparent mortgage risk evaluation system.